Sikkim State Draft Annual Plan 1982-83 - Planning Commission (Planning Commission, 1982)
The revised estimate for the current year were out to Ps. 25.53 crores which to 2.5 crores more then the approved outlay, as far as the resources are- concerned the State's awn contribution consists Rs. 96 lakhs of which Rs. 25 lakhs is in account of borrowing. This amount cannot be realised because formal permission has not been given for the purpose, Rs, 11 lakhs as LIC soon can be realised.
Planning and Development Department, Government of Sikkim